2008
DOI: 10.1590/s0101-81752008000200004
|View full text |Cite
|
Sign up to set email alerts
|

Site fidelity of Sotalia guianensis (Cetacea: Delphinidae) in Sepetiba Bay, Rio de Janeiro, Brazil

Abstract: Estuarine dolphins, Sotalia guianensis (Van Bénéden, 1864), were identified in Sepetiba Bay (22º35'S, 44º03'W), state of Rio de Janeiro, Brazil, between February 1994 and July 2006 using the photo-identification method. A total of 72 surveys resulted in the identification and cataloguing of 217 individual dolphins. Seventy-nine (36%) were resighted at least once during the study period. The average interval between resightings was 40,6 ± 31,1 months. Large numbers of mother-and-calf pairs were recorded during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
2
12
0
3
Order By: Relevance
“…Photo-identification has been extensively applied for studying marine mammals (e.g. Hastings et al, 2008;Nery et al, 2008), sharks and rays (Marshall & Pierce, 2012) and, more recently, has been demonstrated a feasible technique for identification of marine teleost fishes (e.g. Perrig & Goh, 2008;Giglio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Photo-identification has been extensively applied for studying marine mammals (e.g. Hastings et al, 2008;Nery et al, 2008), sharks and rays (Marshall & Pierce, 2012) and, more recently, has been demonstrated a feasible technique for identification of marine teleost fishes (e.g. Perrig & Goh, 2008;Giglio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In both Ilha Grande and Sepetiba bays, Guiana dolphin populations are present throughout the year, and most groups are composed of mothercalf pairs accompanied by juveniles (LODI 2003, NERY et al 2008. At the Ilha Grande Bay, LODI (2003) observed 1,754 individuals in 54 groups; calves were present in 89% of the groups and juveniles in 87% (LODI 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Much of the complex is shallow (~6 m depth), but in some isolated areas, particularly between the islands, water depth can be 47 m (Borges 1990). This ecologically important area is surrounded by more than de delfines Guiana que son consistentemente encontrados durante todo el año; los individuos se han registrados por más de 12 años y probablemente usan la bahía para alimentarse y reproducirse (Nery et al 2008a). Datos sobre la abundancia y fidelidad de hábitat de estos delfines son esenciales para la conservación efectiva y también para fines de manejo, particularmente en áreas costeras y de estuario como es la bahía de Sepetiba, donde las poblaciones humanas se están expandiendo rápidamente, aumentando las amenazas directas e indirectas a los animales (Nery et al 2008b).…”
Section: Methodsunclassified
“…Estimación de abundancia por captura-recaptura de los delfines Guiana en el sureste de Brasil M Freitas Nery 1 *, S Marino Simão all year round; individuals have been recorded for more than 12 years and probably use the bay for feeding and reproduction (Nery et al 2008a). Data on Guiana dolphin abundance and site fidelity are essential for effective conservation and management purposes, particularly in coastal and estuarine areas like Sepetiba Bay, where human populations are rapidly expanding, increasing the direct and indirect threats to dolphins (Nery et al 2008b).…”
Section: Capture-recapture Abundance Estimate Of Guiana Dolphins In Smentioning
confidence: 99%
See 1 more Smart Citation